2006
DOI: 10.1177/0022427806291262
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Community Disadvantage on the Relationship between the Family and Juvenile Crime

Abstract: Prior research on the family has identified many variables significantly associated with criminal involvement, including such things as parental supervision and discipline and the quality of the parent-child relationship. However, little attention has been devoted to the possibility that the effects of these variables on crime depend on characteristics of the social context in which a family resides. Using data from a national sample of adolescents, the authors examined how the effects of key family variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 55 publications
5
54
0
Order By: Relevance
“…However, children from low SES homes tend to have worst academic and developmental results than children from upper classes (Furstenberg et al 1999;Noble et al 2005Noble et al , 2006Noble et al , 2007Sameroff et al 1987b). Furthermore, children from low SES engage more in aggressive and antisocial behaviors (Hay et al 2006;Nobile et al 2007;Noble et al 2005Noble et al , 2007Veenstra et al 2005). Thus, not only is the cost of raising a child high, but for lowresource parents, the expectable social outcome is not commiserated with the effort.…”
Section: Discussionmentioning
confidence: 99%
“…However, children from low SES homes tend to have worst academic and developmental results than children from upper classes (Furstenberg et al 1999;Noble et al 2005Noble et al , 2006Noble et al , 2007Sameroff et al 1987b). Furthermore, children from low SES engage more in aggressive and antisocial behaviors (Hay et al 2006;Nobile et al 2007;Noble et al 2005Noble et al , 2007Veenstra et al 2005). Thus, not only is the cost of raising a child high, but for lowresource parents, the expectable social outcome is not commiserated with the effort.…”
Section: Discussionmentioning
confidence: 99%
“…This reasoning is analogous to that of general theoretical perspectives on crime and delinquency which proposes that individual propensity for crime is more likely to translate into actual criminal behavior for those exposed to crimeprone environments (Agnew et al 2002;Wright et al 2001). In neighborhood research, the proposition that various causes of crime may interact to amplify another's effect is supported by recent studies showing that adolescents with risks on both the neighborhood and family levels were particularly likely to affiliate with deviant peers and to manifest behavior problems (e.g., Beyers et al 2003;e.g., Brody et al 2001e.g., Brody et al , 2003Coley et al 2004;Hay et al 2006;Simons et al 2005). In contrast, studies of the interactive effects between individual and neighborhood character istics on delinquency have been scarce and have produced mixed results.…”
Section: Individual Characteristics and Youth Gangsmentioning
confidence: 99%
“…For example, living in adverse family environments (low family attachment, family cohesiveness, family respect, and family role modeling) has been associated with younger arrests and more arrests by age 17 for males (Ge et al 2001). Additionally, Hay et al (2006) demonstrated a relationship between the family environment and juvenile crime, such that criminally involved youth were more likely to come from families with lower parent-child attachment, parental monitoring and reinforcement of prosocial behavior, and higher use of physical punishment and coercion. These effects were further exacerbated by community disadvantage and poverty, measured both objectively (based on ZIP codes), and subjectively (parents' ratings of their communities).…”
Section: Introductionmentioning
confidence: 99%